2013
DOI: 10.3329/jbsp.v8i1.16646
|View full text |Cite
|
Sign up to set email alerts
|

FEV1, FVC, FEV1/FVC ratio in children of 7-14 years of age from Western Rajasthan

Abstract: Background: The knowledge of pulmonary function tests (PFTs) is a basic requirement to understand the respiratory physiology for all medical physiologists and clinicians Pulmonary Function Tests provide objective evidence of nature and severity of lung disease. Objective: To observe FEV 1 , FVC, FEV 1 /FVC ratio in healthy male and female school children from 7-14 years of age in Western Rajasthan and to find out the relationship of FEV1, FVC, FEV1/FVC ratio with their height, weight, BSA and sex Methods: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Hence, for clinical evaluation of child's lung function, height is the most significant independent parameter in comparison to age and weight. Study by Sharma et al [27] in Indian children and another study by Primhak et al [28] in British children also showed similar findings. PEFR values of children were found to be lesser than that of other South Indian, North Indian, and Western children.…”
Section: Dicsussionsupporting
confidence: 64%
“…Hence, for clinical evaluation of child's lung function, height is the most significant independent parameter in comparison to age and weight. Study by Sharma et al [27] in Indian children and another study by Primhak et al [28] in British children also showed similar findings. PEFR values of children were found to be lesser than that of other South Indian, North Indian, and Western children.…”
Section: Dicsussionsupporting
confidence: 64%
“…While BMI was also higher in boys but it was not significant statistically. Sharma et al in Western Rajasthan in India studied among 7-14 years old school children and found significant difference between male and female children regarding anthropometry 11 . Mean FVC, FEV 1 and PEFR were significantly higher among boys than girls while FEV 1 /FVC ratio was significantly higher among girls in this study which was in line with Doctor et al who have found significant difference between boys and girls regarding FVC, FEV 1 and PEFR 9 .…”
Section: Discussionmentioning
confidence: 99%
“…5 Indian studies also show a similar variability. [7][8][9][10][11][14][15][16][17][18][19][20] A study by Taksande et al shows variation in PEFR values in children from Wardha, Maharashtra as those compared to other parts of the country. 8 PEFR can be assessed efficiently for children mostly above 5 years of age, as below this age there is difficulty in understanding the assessment process and room for error.…”
Section: Discussionmentioning
confidence: 99%
“…The (Table 2) shows comparison of PEFR values of present study with other equivalent Indian studies. 7,19,[25][26][27] This intra-country variability over the years made the authors realize the strong influence of urbanization leading to air pollution, in terms of increasing density of the respirable suspended particulate matter (RSPM), an important factor influencing PEFR. 28 This has also resulted in increased levels of air pollutants exceeding the prescribed standards, in most urban areas.…”
Section: Discussionmentioning
confidence: 99%